2021
DOI: 10.1149/2162-8777/ac202b
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of MWCNTs Decorated with ZnO Nanoparticles as a Novel Additive in Conventional Water-based Drilling Mud

Abstract: The effect of multi-walled carbon nanotubes (MWCNTs) decorated with ZnONPs on the rheological and filtration properties of conventional water-based drilling muds (WBDM) was investigated. ZnONPs and MWCNTs were synthesized separately, then MWCNTs were decorated with ZnONPs by chemical vapor deposition method and characterized by scanning electron microscopy and X-ray photoelectron spectroscopy. Synthesized and characterized ZnONPs/MWCNTs were added to conventional WBDM at a rate of 0.001% to 0.01%, and then rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12] Özkan et al, 13 stated that as a result of their studies in which they added graphene, graphene oxide and AuNPS/GO to drilling mud, both rheological and filtration properties of drilling mud were improved. In the study conducted by Özkan et al, 14 they examined the impact of functionalized zinc oxide nanoparticle material on multi-walled carbon nanotube (MWCNT) and water-based drilling mud. The results showed that adding ZnONPs/MWCNTs to the drilling mud increased its plastic viscosity value by 42.8%, its apparent viscosity value by 31.6%, its yield point value by 28%, its 10 s and 10 min values by 22% and 25%, the cake thickness value by 38.9%, and the filtration loss value decreased by 13.8%.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Özkan et al, 13 stated that as a result of their studies in which they added graphene, graphene oxide and AuNPS/GO to drilling mud, both rheological and filtration properties of drilling mud were improved. In the study conducted by Özkan et al, 14 they examined the impact of functionalized zinc oxide nanoparticle material on multi-walled carbon nanotube (MWCNT) and water-based drilling mud. The results showed that adding ZnONPs/MWCNTs to the drilling mud increased its plastic viscosity value by 42.8%, its apparent viscosity value by 31.6%, its yield point value by 28%, its 10 s and 10 min values by 22% and 25%, the cake thickness value by 38.9%, and the filtration loss value decreased by 13.8%.…”
mentioning
confidence: 99%
“…3 Therefore; It has been observed that the properties of drilling muds are improved by adding nano and micro-sized materials. [4][5][6][7][8][9][10][11][12] Özkan et al (2021), 13 when they investigated the effect of multi-walled carbon nano tube functionalized with zinc oxide nanoparticle material on water-based drilling mud, in their study, drilling mud with the addition of ZnONPs/MWCNTs; the plastic viscosity value increased by 42.8%, the apparent viscosity value increased by 31.6%, the yield point value increased by 28%, the 10 s and 10 min values increased by 22% and 25%, the cake thickness value increased by 38.9%, and the filtration loss value decreased by 13.8%. Özkan, A., in (2020); 14 investigated the possible effects of multi-walled carbon nanotubes containing gold nanoparticles by adding them to water-based drilling mud at different rates.…”
mentioning
confidence: 99%